Allelopathic Effects of Sphaeranthus suaveolens on Seed Germination and Seedling Growth of Phaseolus vulgaris and Oryza sativa - Hudson C. Laizer; Musa N. Chacha; Patrick A. Ndakidemi (Advances in Agriculture)
Weeds with allelopathic effect have been reported to cause significant damage in agriculture particularly in smallholder farming systems. This study assessed the allelopathic effects of different concentrations of crude extract of a noxious weed Sphaeranthus suaveolens on seed germination and seedling growth of Phaseolus vulgaris and Oryza sativa by examining germination, seedling height, and total chlorophyll content after seven and fourteen days of crude extract treatment, respectively. Results showed that seed germination and seedling growth were significantly (p<0.001) decreased with increase in concentration of crude extract, signifying concentration dependency. Highest concentration (100%) of S. suaveolens crude extracts resulted in 90% and 100% inhibition of P. vulgaris and O. sativa seed germination, respectively. Chlorophyll content, fresh weight, and root and shoot length of both P. vulgaris and O. sativa were also significantly (p<0.001) affected by highest concentration (100%) of S. suaveolens crude extracts. Results from this study suggest that the extract of S. suaveolens contains water-soluble allelochemicals which significantly reduce growth and productivity of P. vulgaris and O. sativa.